Primary thyroid hemangioma: a case report and literature review - Fattahi Masuom, Seyed Hossein; Amirian-Far, Azam; Rezaei, Reza (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2021)
Hemangioma is a benign vascular neoplasm characterized by capillary proliferation, which is more common in children with a prevalence of 4–5% [1]. Hemangiomas are more likely to be present in the head and neck region (65% of cases) and may occur in any organ of the body, such as the skin, subcutaneous tissue, tongue, brain, and liver, but are extremely rare in the thyroid gland [2]. Most cases of thyroid hemangiomas are secondary to neck procedures such as fine-needle aspiration (FNA) or neck trauma that results from the formation of a hematoma [3]. On the other hand, primary thyroid hemangioma is a developmental anomaly due to the lack of canal formation by angioblastic mesenchyma [4]. These tumors have no obvious clinical manifestations other than cervical mass and no distinct imaging signs are seen with ultrasound or computed tomography (CT) scans. In almost all patients, the diagnosis depends on postoperative histopathology [5]. Here, we report a rare case of thyroid hemangioma in which the retrosternal goiter was suspected preoperatively and review the associated literature.